PSYCHIATRY-PAST, PRESENT & FUTURE - Doongaji, Dinshaw R. (Medknow Publications, 1997)
An overview of psychiatry during the last three decades as practised in a general teaching hospital is presented. Psychiatry as an academic subject has matured tremendously during this period. The empirical treatments of the 1950s and the 1960s which evoke nostalgic memories, have been replaced by modern methods of treatment. However, there is a need to exercise caution against the blind acceptance of new and sophisticated research findings in biological psychiatry. Inspite of the bright future facing psychiatry, the identity of psychiatry as a medical discipline must be preserved at all cost. Psychiatrists should also realise the dangers of gradual fractionation and impersonalisation which threatens the speciality, and makes all possible efforts to prevent this.